Phenolic phytochemistry, in vitro, in silico, in vivo, and mechanistic anti-inflammatory and antioxidant evaluations of Habenaria digitata - Almasoudi, Hassan Hussain; Saeed Jan, Muhammad; Nahari, Mohammed H.; Alhazmi, Abdulfattah Yahya M.; Binshaya, Abdulkarim S.; Abdulaziz, Osama; Mahnashi, Mater H.; Ibrar, Muhammad; Zafar, Rehman; Sadiq, Abdul (Frontiers in Pharmacology, 2024)
The excessive and imbalance of free radicals within the body lead to inflammation. The objective of the current research work was to explore the anti-inflammatory and antioxidant potentials of the isolated compounds from H. digitata. In this study, the isolated phenolic compounds were investigated for in-vitro and in-vivo antiinflammatory potentials along with antioxidant enzyme. The anti-inflammatory and antioxidant potentials of the phenolic compounds were assayed via various enzymes like COX-1/2, 5-LOX and ABTS, DPPH and H2O2 free radical enzyme inhibitory assay. These compounds were also explored for their in-vivo antioxidant activity like SOD, CAT, GSH-Px, MDA level in brain, heart and liver. The anti-inflammatory potential was evaluated using carrageenan-induced pleurisy model in mice. On the basis initial screening of isolated compounds, the most potent compound was further evaluated for the anti-inflammatory mechanism. Furthermore, molecular docking study was also performed for the potent compound. The phenolic compounds were isolated and identified by using GC-MS/NMR analysis by comparison its spectra to the library spectra. The isolated phenolic compounds from H. digitata were 5-methylpyrimidine-24,4-diol (1), 3,5-dihydroxy-6-methyl-2,3-dihydropyran-4-one (2), 2-isopropyl-5methylphenol (3), 3-methoxy-4-vinylphenol (4) and 2,6-dimethoxy-4-vinylphenol (5). In in-vitro antioxidant assay, the most potent compound was compound 1 causing IC50 value against ABTS, DPPH and H2O2 was 0.98, 0.90 and 5 µg/mL respectively. Similarly, against COX1/2 and 5-LOX the compound 1 was again the potent compound with IC50 values 42.76, 10.70, 7.40 µg/mL. Based on the in-vitro results, compound 1 was further evaluated for in-vivo antioxidant and anti-inflammatory potentials. Findings of the study suggest that H. digitata contains active compounds with potential antiinflammatory and antioxidant effect. These compounds could be screened as drug candidates for pharmaceutical research targeting conditions associated with oxidative stress and inflammatory conditions in medicinal chemistry study as well as support ethnomedicinal use for inflammation and oxidative stress.